2021
DOI: 10.1063/5.0038047
|View full text |Cite
|
Sign up to set email alerts
|

Significant bonding rearrangements triggered by Mg4 clusters

Abstract: Among new nanostructures with exciting reactivity features, Mg4 clusters present a promising catalytic behavior. The structure, stability and bonding of the complexes formed by the interaction of Mg4 clusters and first row Lewis bases, namely ammonia, water and hydrogen fluoride, have been investigated through the use of high-level G4 single-reference and CASPT2 multireference formalisms. The adducts formed reflect the high electrophilicity of the Mg4 cluster through holes in the neighborhood of each metallic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…The reactants were studied, and each tip on the IRI 2D graphic represent the formation of bonds. The Mg 4 cluster on the IRI 3D graphic agree with the research findings, which proves that the Mg 4 cluster and H 2 O adsorb chemically in fact [51]. When sing(λ 2 )ρ<0, the density of the scatters show the strength of the interaction, and the denser the scatters, the stronger the week interaction.…”
Section: Interaction Region Indicator Function (Iri)supporting
confidence: 86%
“…The reactants were studied, and each tip on the IRI 2D graphic represent the formation of bonds. The Mg 4 cluster on the IRI 3D graphic agree with the research findings, which proves that the Mg 4 cluster and H 2 O adsorb chemically in fact [51]. When sing(λ 2 )ρ<0, the density of the scatters show the strength of the interaction, and the denser the scatters, the stronger the week interaction.…”
Section: Interaction Region Indicator Function (Iri)supporting
confidence: 86%
“…22–27 Vos et al . 28,29 reported a high level of single-reference and multi-reference ab initio calculations showing that Be 4 clusters exhibit very efficient Lewis acids when interacting with conventional Lewis bases such as ammonia, water, or hydrogen fluoride. The corresponding acid–base interactions trigger the sequential dissociation of all Lewis bases.…”
Section: Introductionmentioning
confidence: 99%
“…As doped, Be atoms effectively improve the NLO reaction, thermodynamics, and hydrogen adsorption properties of Al 12 N 12 nanoclusters, which were found in the study of Mehboob et al 21 Recent studies on two-dimensional structures, clusters and visible-light-driven photocatalytic hydrogen evolution reactions are also effective methods for developing hydrogen energy. [22][23][24][25][26][27] Vos et al 28,29 reported a high level of single-reference and multireference ab initio calculations showing that Be 4 clusters exhibit very efficient Lewis acids when interacting with conventional Lewis bases such as ammonia, water, or hydrogen fluoride. The corresponding acid-base interactions trigger the sequential dissociation of all Lewis bases.…”
Section: Introductionmentioning
confidence: 99%